Students' Ability in Practicing L & R Pronunciation in English with a Song: A Literature Review - Wiwit Akriani; Yeti Dewanti; Lenni Astuti (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
Pronunciation is a fundamental component of English language learning that directly affects learners’ intelligibility and communicative competence. Among EFL learners, particularly those from Indonesian backgrounds, the pronunciation of the English phonemes /l/ and /r/ poses a persistent challenge due to first language interference, limited phonological awareness, and insufficient exposure to native-like input. Objective: This study aims to review and synthesize existing literature on students’ ability to practice English pronunciation, specifically the /l/ and /r/ sounds, through the use of songs as a learning medium. Method: Employing a qualitative literature review approach, this study analyzes findings from peer-reviewed journal articles, conference proceedings, and relevant academic sources related to pronunciation instruction, phonological difficulties, and song-based language learning. Results: The review reveals that songs provide repetitive, rhythmic, and authentic phonological input that supports pronunciation development while fostering a low-anxiety and motivating learning environment. Although previous studies highlight the positive impact of songs on learners’ engagement and pronunciation accuracy, research focusing explicitly on /l/ and /r/ pronunciation remains limited. Conclusion: Therefore, further empirical investigation is recommended to strengthen instructional practices in EFL pronunciation teaching.